Adrenal Androgens and Androgen Precursors—Definition, Synthesis, Regulation and Physiologic Actions. Issue 4 (30th September 2014) - Turcu, Adina; Smith, Joshua M.; Auchus, Richard; Rainey, William E.
Abstract: The human adrenal produces more 19 carbon (C19 ) steroids, by mass, than either glucocorticoids or mineralocorticoids. However, the mechanisms regulating adrenal C19 steroid biosynthesis continue to represent one of the most intriguing mysteries of endocrine physiology. This review will discuss the C19 steroids synthesized by the human adrenal and the features within the adrenal that allow production of these steroids. Finally, we consider the effects of these steroids in normal physiology and disorders of adrenal C19 steroid excess. © 2014 American Physiological Society. Compr Physiol 4:1369‐1381, 2014.